STUDY OF VASCULAR ACCESS IN HAEMODIALYSIS PATIENTS USING ULTRASONOGRAPHY - Tiron, O.I.; Ancheva, I.A.; Mokriienko, E.M.; Movlyanova, N.V.; Lazor, N.V.; Vastyanov, R.S. (World of Medicine and Biology, 2025)
The purpose of this study was to evaluate the efficacy of arteriovenous fistula using ultrasound technique in patients undergoing haemodialysis, taking into account their anamnesis analysis and their psychological state assessment. The study involved 76 patients with chronic kidney disease aged 25 to 70 years. During the ultrasound assessment of arteriovenous fistula in patients, the diameter, lumen, compressibility of the vein and its location relative to the skin were analyzed, as well as the feeding artery was examined. Bloodflow assessment in vascular access was performed using colour Doppler mapping and pulse dopplerometry. In patients without complications in vascular access, the average diameter of the feeding artery was 4.3±1.4 mm. The diameter of the anastomosis ranged from 1.4 mm to 10 mm. The volumetric bloodflow rate in the vascular access was from 500 ml/min to 1600 ml/min which corresponds to the standard values for a functioning arteriovenous fistula. Anatomical and individual tissue characteristics of each patient and concomitant diseases reduce the efficacy of fistula and increase the risk of complications. Ultrasonography allows for the timely detection of anatomical and functional changes affecting the effectiveness of hemodialysis, which makes this method a valuable tool for diagnostics and monitoring. Authors conclude that ultrasound Doppler study is the main method for vascular access monitoring in the complex management of patients receiving renal replacement therapy. Evaluation of the psychological state of patients on hemodialysis showed a decrease in interest in life, a feeling of dissatisfaction, despair, hopelessness and fear for the future, which worsened during the outbreak of military actions in Ukraine.